Association between the gut microbiota and diabetic nephropathy: a two-sample Mendelian randomization study - Wenjie Dong; Qiuyu Li; Lei Chen; Hui Tang; Kun Tu; Li Luo; Longyang Jiang; Yilan Huang (Renal Failure)
Numerous studies have revealed a correlation between the risk of developing diabetic nephropathy (DN) and the gut microbiota (GM) composition. However, it remains uncertain whether the GM composition causes DN. We aimed to explore any potential causal links between the GM composition and the risk of developing DN. A meta-analysis conducted by the MiBioGen consortium of the largest genome-wide association study (GWAS) provided aggregated data on the GM. DN data were obtained from the IEU database. The inverse-variance weighting (IVW) method was employed as the primary analytical approach. The IVW analysis indicated that genus Dialister (OR = 0.51, 95% CI: 0.34–0.77, p = 0.00118) was protective against DN. In addition, class Gammaproteobacteria (OR = 0.47, 95% CI: 0.27–0.83, p = 0.0096), class Lentisphaeria (OR =0.76, 95% CI: 0.68–0.99, p = 0.04), order Victivallales (OR = 0.76, 95% CI: 0.58–0.99, p = 0.04), and phylum Proteobacteria (OR = 0.53, 95% CI: 0.33–0.85, p = 0.00872) were negatively associated with the risk of developing DN. Genus LachnospiraceaeUCG008 (OR =1.45, 95% CI: 1.08–1.95, p = 0.01), order Bacteroidales (OR = 1.59, 95% CI: 1.02–2.49, p = 0.04), and genus Terrisporobacter (OR = 1.98, 95% CI: 1.14–3.45, p = 0.015) were positively associated with the risk of developing DN. In this study, we established a causal relationship between the genus Dialister and the risk of developing DN. Further trials are required to confirm the protective effects of probiotics on DN and to elucidate the precise protective mechanisms involving genus Dialister and DN.